The state of race : Asian/American fiction after World War II - Ang, Sze Wei, 1978- (SUNY series in multiethnic literature., 2019)
"Contemporary ideas about race are often assumed to be products of specific locales and histories, and yet we find versions of the same ideas about race across countries and cultures. How can we account for this paradox? In The State of Race, Sze Wei Ang argues that globalization has led to new ways of using racial stereotypes as shorthand for complex social relations in disparate national contexts. Literature then provides a key to understanding these tropes and the role that race has played in shoring up state power since World War II. In an era marked by global economic dependence the nation-state has only become more rather than less central to organizing social life. It does so, Ang argues, via notions and tropes of race that cast human and cultural differences in morally charged terms. Focusing on a series of Asian American and Malaysian texts, Ang tracks the significance of two figures in particular--the model minority and the communist spy. Appearing in novels, politics, and popular culture, these tropes anchor powerful narratives about race, global capital, and state sovereignty. In exploring how two countries that seem not to have much in common--the U.S. and Malaysia--nonetheless share very similar ways of conceptualizing race, Ang sheds light on an emerging global story of value, that is to say, a story of who does and does not have value, in both ethical and economic senses of the term, in the eyes of the state"--